The Role of Psychological Contract, Organizational Commitment, and Organizational Politics in Enhancing Employee Performance - Yuliani , Yeni ; Rizki, Muhammad Irfan (ARE Publisher, 2025)
Objectives: This research intends to examine how psychological contracts, organizational commitment, and political organizations on employee performance at BDP, a company engaged in office space rental, building and asset management, construction services, outsourcing, and security.Methodology: By employing a numerical method, information was gathered from workers at PT BDP and examined to investigate the connection between different factors.Findings: The findings of the research indicate that the agreements between employees and their employers, along with their dedication to the organization, greatly and positively affect how well employees perform. Moreover, effectively run political organizations also play a role in enhancing employee performance.Conclusion: These findings emphasize the importance of effective management strategies in maintaining psychological contracts, strengthening organizational commitment, and managing organizational politics to enhance employee productivity.